30 day outcome after early discharge in low risk ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention. (3rd May 2023) - Gjana, A; Pavli, E; Kristo, A; Vasili, E; Duka, A; Shuka, N; Voci, A; Pane, E; Zaimi, G; Kastrati, A; Dibra, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Current guidelines for management of patients with ST-segment elevation myocardial infarction (STEMI) encourage an early discharge (48-72 h) after a successful primary percutaneous coronary intervention (PCI) in selected low risk patients. Yet, this strategy is not routinely applied. The evidence on the relative outcome of patients discharged early compared to those discharged later, has been limited. Purpose: To assess safety of early discharge in low risk STEMI patients treated with primary PCI by analyzing 30 days outcomes relative to early and late discharge strategies. Methods: We prospectively enrolled 109 patients presented with STEMI from April 2019 to September 2019, who were categorized as low risk according to Zwolle risk score. 60 (55%) patients were discharged after 48-72 hours and 49 (45%) after > 72 hours. We gathered clinical data at 30 days. Primary endpoints were occurrence of a major adverse event - a composite of death from any cause, nonfatal myocardial infarction and acute stent thrombosis. Secondary endpoints were acute angina and re-hospitalization. Results: The mean age was 59.7 +/- 10.5 years in early discharge group compared to 62.8 +/- 10.5 years in late discharge group (p=0.132). 88 (80.7%) patients were male. 58 (53.2%) of them had inferior MI. Mean ejection fraction was 49.25% +/- 4.95%. Median symptom to balloon time was 9.3 +/- 6.7 hour. Median length of stay was 3.4 days +/-0.6. Primary endpoint occurred in one patient in the early discharge group, who had acute stent thrombosis and nonfatal myocardial infarction. No death from any cause was observed in both groups. Secondary endpoint occurred in 3 patients who had acute angina, 2 in late discharge group and 1 in early discharge group. Conclusion(s): Data from our study reveal that an early discharge strategy in selected low risk STEMI patients treated with successful primary PCI is not associated with a significant increase in major adverse events compared to late discharge strategy.